Seismic Performance of Reinforced Concrete Structures with Concrete Deficiency Caused by In-situ Quality Management Issues - Areen Aljaafreh; Yazan Alzubi; Eslam Al-Kharabsheh; Bilal Yasin (Salehan Institute of Higher Education, 2023)
Concrete is a widely used building material known for its cost-effectiveness and high resistance compared to alternative materials. However, uncertainties in the casting process due to variations in the environment and human error can compromise its strength, increasing the risk of collapse when subjected to seismic excitations. Previous studies have demonstrated the detrimental effects of earthquake vibrations on buildings and infrastructure. This study aims to fill the research gap by investigating the seismic behavior of reinforced concrete (RC) structures constructed with lower-quality concrete under near-fault pulse-like ground motions. The main objective of this research is to assess the impact of diminished concrete strength on structural rigidity and susceptibility to ground disturbances. Specifically, the study aims to quantify the extent of performance changes in defective structures, particularly those constructed with poor-quality concrete, in response to seismic activities. To achieve this, the research involves developing multiple finite element models and conducting nonlinear analysis to scrutinize their behavior. A key focus of the study is to compare the performance of various RC buildings with concrete defects to that of a benchmark model. This comparative analysis highlights the influence of suboptimal quality control on the nonlinear behavior of RC structures. Furthermore, the study examines the correlation between changes in building response and earthquake characteristics to provide comprehensive insights into the potential risks associated with substandard construction practices. Based on the results of this study, it was found that inadequate quality control of concrete significantly impacts the performance of RC frames subjected to pulse-like ground motions. The decrease in compressive strength of the concrete led to noticeable increases in various structural parameters, including story shear, overturning moments, story displacement, drifts, accelerations, and hysteretic energy. These findings highlight the detrimental effects of compromised concrete quality on the overall structural response.Â Doi: 10.28991/CEJ-2023-09-08-010 Full Text: PDF